'n Evaluasie van die uitvoering van optimale boerderyplanne verkry uit die toepassing van 'n geintegreerde boerderybeplanningsbenadering in die Kroonstad omgewing - Van Der Westhuizen, Carlu (University of the Free State, 1989)
Integrated farm planning was done by H.F. Hugo on the farms of 29 farmers during a previous study in 1985 entitled "'n Opbrengs-koste-vergelyking van die lineere programmeringstegniek vir plaasbeplanning op plaasvlak in die Kroonstad-omgewing". In conjunction with the farmer use was made of experts from different disciplines by integrating their knowledge to do farm planning on the basis of total integrated farm planning. The linear programming technique (with the aid of a computer) was used to obtain an optimal farm plan for every farmer. The variable planning cost amounted to R2485,31 per farmer while the expected income cost ratio was 1,757. The most important prerequisite for obtaining this income cost ratio was that the optimal farm plans were implemented by the farmers. For this study three objectives were formulated namely - i) the extent to which the optimal farm plans were implemented by the farmers; ii) the reasons should the plan not be implemented in full; and iii) guidelines for future planning. It was found that on all farms the average implementation over regarding numbers/areas, presented three years after the farmers received their planning recommendations, was 65,4 percent. Up to 1986 the average was 75,4 percent for cash crops, 45,4 percent for artificial pastures, 65,5 percent for cattle and 42,7 percent for sheep. Significant differences were found between farmers regarding the implementation of the plans. In addition to the numbers/areas, the degree of implementation regarding the composition of enterprises and production practices was also measured. The majority of farmers indicated that the composition of their cash crops and planted pastures changed moderately to a great deal. Contrary to this the change in the composition of livestock was either small or no change took place at all. Concerning production practices the majority of farmers were of the opinion that there was no change in their practices. Many reasons were given as to why the plans were not implemented in full. Some of these reasons were not taken into account thoroughly enough during planning while it was impossible to make provision for others. The main mistakes that occurred during planning were that the prescribed steps in integrated farm planning were not complete and that they were not executed correctly. In the light of the fact that integrated farm planning is essentially a sequence of short-term plans that aim to fulfil a long-term objective, and the fact that only a long-term plan was provided, it was obvious quite early in this study that farmers would have bridging problems. These problems were mainly solved while the agricultural economist was closely involved with the farmers, but when he quit his job, implementation almost came to a standstill. The fact that the personal preferences of farmers were not taken into account sufficiently, as well as the problem that new production practices were used by farmers, were major faults that must be taken into account properly during future planning actions. Contact between the planner and the farmers was inadequate because communication took place through the agricultural economist and not directly between the planner and the farmers. During the time that the Hugo study was implemented, the fact that there was a major drought, and dramatic increases in interest rates and input costs while product prices stayed the same or declined, had a constraining effect on implementation. Regarding the infrastructure, it seems that too many institutions were involved in the planning process and that planning took place on an individual basis instead of the underlying principle of planning on an integrated multidisciplinary foundation. One solution could be for co-operatives to have their own planning teams that can do integrated farm planning in an integrated way. Alternatively, the Department of Agricultural Development could operate in the same way, as is currently envisaged by the ADC-system (Agricultural Development centres). Should a collaboration between more than one institution be required special care must be taken to prevent the mistakes that are outlined in this study. If repetition of integrated farm planning is done annually in terms of a new short-term plan that incorporates current product prices and input cost, as well as the physical and financial condition of the farm at that time, meaningful integrated farm planning can be carried out and a high degree of implementation can be achieved.
Dissertation (M.Sc.Agric. (Agricultural Economics))--University of the Free State, 1989
Keywords: Farm layout -- South Africa -- Kroonstad; Farm management -- -- South Africa -- Kroonstad; Agricultural administration -- South Africa -- Kroonstad